A high-strength low-alloy wear-resistant steel and a preparation method thereof
A high-strength low-alloy steel is produced using a simplified middle-frequency electromagnetic induction melting and casting process, followed by heat treatment, addressing the complexity and cost issues of existing methods by achieving high hardness and toughness for wear-resistant steel teeth.
Patent Information
- Application Number
- CN202311132394.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Current methods for developing high-strength, wear-resistant steel teeth for engineering machinery involve complex processes such as heat treatment and alloying, leading to long production cycles and high costs, with existing materials lacking sufficient hardness and toughness.
A high-strength low-alloy steel is produced through a short process of middle-frequency electromagnetic induction melting and casting, followed by simple heat treatment, resulting in a microstructure predominantly composed of martensite with residual austenite and carbide particles, enhancing hardness and toughness.
The process simplifies production, reduces costs by using lower amounts of expensive elements, and achieves a hardness of ≥52 HRC and impact absorption of ≥16 J, while maintaining high strength and toughness, making it suitable for wear-resistant components.
Smart Images

Figure CN116926437B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant steel, and in particular relates to a high-strength low-alloy wear-resistant steel and a preparation method thereof. Background Art
[0002] Engineering machinery is an important reflection of a country's international competitiveness and is constantly developing towards large-scale and high-end. Wear-resistant components are the core components of engineering machinery such as tunneling, grinding, and crushing, which directly affect the working efficiency of the machinery. Bucket teeth are key consumable parts for excavators to achieve rock breaking, loosening and excavation operations. During the working process, bucket teeth not only suffer from severe abrasive wear, but also have to withstand certain impact loads. Their lifespan is often very short, and their failure forms include wear, deformation, and fracture, with huge consumption. Therefore, the development of new bucket tooth materials with high hardness, wear resistance and deformation resistance is an important trend for the efficient operation of related machinery.
[0003] Patent CN202310187646.4 discloses a heat treatment method for wear-resistant bucket teeth for super-large excavators. Medium-carbon low-alloy steel and medium-carbon medium-alloy steel undergo bainite transformation isothermal treatment or quenching treatment and then further partitioning treatment to obtain bainite + martensite or martensite wear-resistant steel. Although the performance is good, the isothermal treatment and partitioning treatment increase the process and make the process control difficult.
[0004] Patent CN201610132309.5 discloses a high-toughness excavator bucket tooth and its production method, the composition is: C: 0.25-0.35, Si: 0.4-0.6, Mn: 0.9-1.1, Cr: 0.85-0.95, Mo: 0.3-0.4, Cu: 0.05-0.10, Ni: 0.10-0.20, P: 0-0.01, S: 0-0.01, the rest is Fe and inevitable impurities. The material has a good toughness match, but its hardness still needs to be improved, and it also involves isothermal treatment, and the process is more complicated.
[0005] Patent CN202011161578.7 discloses a highly wear-resistant and high-strength and toughness steel bar for excavator bucket teeth and a preparation method thereof, wherein the chemical composition is: C: 0.18%~0.22%, Si: 2.1%~2.5%, Mn: 2.8%~3.2%, Cr: 0.35%~0.55%, Mo: 0.07~0.13%, Ni: 0.35%~0.45%, V: 0.010%~0.015%, Ti: 0.06%~0.10%, B: 0.0015%~0.0035%, N: 0.010%~0.015%, Al: 0.035%~0.065%, P≤0.015%, S≤0.010%, and the remainder is Fe. The steel bar is refined by LF+VD to obtain steel billets, which are then continuously cast and rolled to obtain steel bars for bucket teeth. The process is relatively long, and the high alloy content brings certain cost increases.
[0006] At present, the main idea of designing new wear-resistant steel for bucket teeth is to use a series of heat treatments to control the final medium and low carbon alloy steel to a bainite or martensite-containing multiphase structure. However, there are often problems such as a long process and difficult to control process structure. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention does not require complex and long-process deformation processing methods such as converters, refining, forging, and rolling. It is directly prepared by short-process melting and casting in a medium-frequency induction furnace and then simple heat treatment, so that the low-alloy wear-resistant steel obtains a high proportion of martensite structure. It has the characteristics of high strength, high hardness and good toughness, and can meet the needs of wear-resistant parts such as engineering machinery bucket teeth.
[0008] The high-strength low-alloy wear-resistant steel of the present invention has the following chemical components by mass percentage: C: 0.28-0.38%, Mn: 1.2-1.5%, Si: 1.6-2.2%, Cr+Mo<1%, V: 0.005-0.015%, rare earth Re: 0.002-0.01%, S≤0.03%, P≤0.03%, and the balance is iron and inevitable impurities.
[0009] Preferably, the final structure of the high-strength low-alloy wear-resistant steel consists of martensite, residual austenite and a small amount of carbide particles, the martensite is lath martensite, and the volume fraction of martensite is ≥92%.
[0010] Preferably, the high-strength low-alloy wear-resistant steel has a hardness of ≥52 HRC, an impact absorption energy of ≥16 J at room temperature, and a tensile strength of ≥1800 MPa.
[0011] The present invention also provides a method for preparing high-strength low-alloy wear-resistant steel, comprising the following steps:
[0012] (1) Mix scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum, ferrovanadium, etc. according to the chemical composition ratio of high-strength low-alloy wear-resistant steel, and then smelt them in a medium-frequency induction furnace. After deoxidation and slag removal, qualified molten steel is obtained, and the temperature of the molten steel is raised to 1620-1650°C;
[0013] (2) Preheat the granular lanthanum-cerium alloy by drying at 200°C and evenly spread it on the bottom of the ladle. Then pour the molten steel obtained in step (1) into the ladle and let it stand for a long time for modification;
[0014] (3) The molten steel modified in step (2) is poured into a casting at a temperature of 1540-1580°C. After the casting is cooled to below 200°C, heat treatment is performed in sequence to obtain high-strength low-alloy wear-resistant steel.
[0015] Preferably, the specific steps of heat treatment in step (3) are as follows:
[0016] 1) Homogenization annealing treatment: heating the low alloy wear-resistant steel to 950-1000°C at a rate of ≤80°C / h, and then cooling to room temperature in the furnace;
[0017] 2) Quenching treatment: the annealed steel is heated to 900-950°C at a rate of 80-100°C / h and then water-cooled to room temperature;
[0018] 3) Tempering treatment: The steel parts after the above quenching treatment are heated to 100-300℃ at a rate of ≤80℃ / h and then taken out of the furnace and air-cooled to room temperature.
[0019] Preferably, when the water is cooled to room temperature in step 2), the water pool needs to be fully stirred, and the water temperature does not exceed 60° C. during the quenching process.
[0020] Preferably, the heat treatment holding time is calculated according to the thickness of the casting, and the calculation method is (1+(thickness / 20mm)*1) hours. During the heat treatment, the spacing between the stacked steel parts is ≥2*thickness.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The high-strength low-alloy wear-resistant steel of the present invention has a low alloy element content, and is mainly composed of low-cost Si and Mn elements, while the content of high-cost elements such as Mo and V is low. Therefore, the wear-resistant steel of the present invention has the advantage of low cost.
[0023] The present invention further refines the structure and promotes the precipitation of fine carbides by adding a very small amount of V element to improve the strength of the steel and ensure toughness; at the same time, by performing a relatively low-cost lanthanum-cerium rare earth element modification treatment in a ladle, the toughness of the high-strength steel is further improved to ensure the safety of the prepared wear-resistant components.
[0024] The present invention adds a certain amount of Si element to ensure the strengthening effect, which makes it easy to generate ferrite in the organization, and it is easy to generate bainite organization in the subsequent quenching process. Therefore, the present invention ensures that the elements are fully diffused and segregation is reduced through homogenization annealing at a sufficient time and temperature, and further ensures that more than 92% of martensite is generated through water quenching at a sufficient temperature after complete austenitization. In this way, the hardness of the wear-resistant steel is guaranteed.
[0025] The present invention does not require complicated and long-process deformation processing methods such as converters, refining, forging, and rolling. It is directly prepared by short-process melting and casting in a medium-frequency induction furnace and then simple heat treatment. The process is simple and easy to industrialize. The hardness of the high-strength low-alloy wear-resistant steel of the present invention is ≥52HRC, the room temperature impact absorption energy (V-notch) is ≥16J, and the tensile strength is ≥1800MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope organization diagram of the high-strength low-alloy wear-resistant steel of the present invention. Implementation
[0027] The present invention is further described in detail below with reference to specific embodiments. Example
[0028] A high-strength low-alloy wear-resistant steel, the chemical composition of which is as follows by mass percentage: C: 0.36%, Mn: 1.4%, Si: 2.2%, Cr: 0.6%, Mo: 0.3%, V: 0.01%, rare earth Re: 0.01%, S≤0.03%, P≤0.03%, and the balance is iron and inevitable impurities.
[0029] The preparation method thereof is specifically as follows:
[0030] (1) Scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum, ferrovanadium, etc. are mixed according to the alloy content ratio and smelted in a medium frequency induction furnace. After deoxidation and slag removal, qualified molten steel is obtained and the temperature of the molten steel is raised to 1650°C;
[0031] (2) Spreading the pre-baked granular rare earth lanthanum-cerium alloy evenly on the bottom of the ladle, pouring the molten steel in step (1) into the ladle, and letting it stand for a long time;
[0032] (3) The molten steel obtained in step (2) is poured into a casting at 1580°C. After the casting is cooled to below 200°C, the casting is heated to 1000°C in a heat treatment furnace at a rate of 80°C / h, kept at this temperature for 4 hours, and then cooled to room temperature with the furnace; then the casting is heated to 950°C at a rate of 100°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and water-cooled to room temperature; finally, the steel piece is heated to 150°C at a rate of 60°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and air-cooled to room temperature, thereby obtaining a high-strength low-alloy wear-resistant steel. Example
[0033] A high-strength low-alloy wear-resistant steel, the chemical composition of which is as follows by mass percentage: C: 0.28%, Mn: 1.5%, Si: 1.9%, Cr: 0.4%, Mo: 0.5%, V: 0.006%, rare earth Re: 0.007%, S≤0.03%, P≤0.03%, and the balance is iron and inevitable impurities.
[0034] The preparation method thereof is specifically as follows:
[0035] (1) Scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum, ferrovanadium, etc. are mixed according to the alloy content ratio and smelted in a medium frequency induction furnace. After deoxidation and slag removal, qualified molten steel is obtained and the temperature of the molten steel is raised to 1620°C;
[0036] (2) Spread the pre-baked granular rare earth lanthanum-cerium alloy evenly on the bottom of the ladle. Pour the molten steel in step (1) into the ladle and let it stand for a long time;
[0037] (3) The molten steel obtained in step (2) is poured into a casting at 1540°C. After the casting is cooled to below 200°C, the casting is heated to 950°C in a heat treatment furnace at a rate of 80°C / h, kept at this temperature for 4 hours, and then cooled to room temperature with the furnace; then the casting is heated to 910°C at a rate of 100°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and water-cooled to room temperature; finally, the steel piece is heated to 250°C at a rate of 60°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and air-cooled to room temperature, thereby obtaining high-strength low-alloy wear-resistant steel; Example
[0038] A high-strength low-alloy wear-resistant steel, the chemical composition of which is as follows by mass percentage: C: 0.33%, Mn: 1.2%, Si: 1.8%, Cr: 0.5%, Mo: 0.4%, V: 0.012%, rare earth Re: 0.004%, S≤0.03%, P≤0.03%, and the balance is iron and inevitable impurities.
[0039] The preparation method thereof is specifically as follows:
[0040] (1) Scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum, ferrovanadium, etc. are mixed according to the alloy content ratio and smelted in a medium frequency induction furnace. After deoxidation and slag removal, qualified molten steel is obtained and the temperature of the molten steel is raised to 1630°C;
[0041] (2) Spread the pre-baked granular rare earth lanthanum-cerium alloy evenly on the bottom of the ladle. Pour the molten steel in step (1) into the ladle and let it stand for a long time;
[0042] (3) The molten steel obtained in step (2) is poured into a casting at 1560°C. After the casting is cooled to below 200°C, the casting is heated to 980°C in a heat treatment furnace at a rate of 80°C / h, kept at this temperature for 4 hours, and then cooled to room temperature with the furnace; then the casting is heated to 930°C at a rate of 100°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and water-cooled to room temperature; finally, the steel piece is heated to 200°C at a rate of 60°C / h, kept at this temperature for 4 hours, and then taken out of the furnace and air-cooled to room temperature, thereby obtaining high-strength low-alloy wear-resistant steel;
[0043] Comparative Example 1
[0044] A wear-resistant alloy steel, the mass percentage of chemical components is: C: 0.36%, Mn: 1.4%, Si: 2.2%, Cr: 0.6%, Mo: 0.3%, S≤0.03%, P≤0.03%, the balance is iron and inevitable impurities. Compared with Example 1, Comparative Example 1 does not contain V and rare earth Re. The preparation method of Comparative Example 1 is consistent with Example 1 except that rare earth lanthanum cerium is not modified.
[0045] Comparative Example 2
[0046] A wear-resistant alloy steel, the mass percentage of chemical components is: C: 0.25%, Mn: 1.4%, Si: 2.2%, Cr: 0.6%, Mo: 0.3%, V: 0.01%, rare earth Re: 0.01%, S≤0.03%, P≤0.03%, the balance is iron and inevitable impurities. Compared with Example 1, the C content of this comparative example is lower, and the preparation method is consistent with Example 1.
[0047] Comparative Example 3
[0048] A wear-resistant alloy steel, the chemical composition by mass percentage is: C: 0.36%, Mn: 1.4%, Si: 2.2%, Cr: 0.6%, Mo: 0.3%, V: 0.01%, rare earth Re: 0.01%, S≤0.03%, P≤0.03%, the balance is iron and inevitable impurities. The specific preparation method is:
[0049] (1) Scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum, ferrovanadium, etc. are mixed according to the alloy content ratio and smelted in a medium frequency induction furnace. After deoxidation and slag removal, qualified molten steel is obtained and the temperature of the molten steel is raised to 1650°C;
[0050] (2) Spread the pre-baked granular rare earth lanthanum-cerium alloy evenly on the bottom of the ladle. Pour the molten steel in step (1) into the ladle and let it stand for a long time;
[0051] (3) pouring the molten steel obtained in step (2) into a casting at 1580°C, and after the casting is cooled to below 200°C, heating the obtained low alloy wear-resistant steel casting to 950°C at a rate of 100°C / h, keeping the temperature for 4 hours, and then cooling it to room temperature with water; finally heating the steel casting to 150°C at a rate of 60°C / h, keeping the temperature for 4 hours, and then cooling it to room temperature with air, thereby obtaining the low alloy wear-resistant steel;
[0052] This comparative example is different from Example 1 only in the heat treatment, where the homogenization annealing heat treatment is removed.
[0053] Performance Testing
[0054] The mechanical properties and martensite volume fraction of the examples and comparative examples were tested with reference to the following standards. The test results are shown in Table 1.
[0055] The tensile test is carried out in accordance with GB / T228-2010 Tensile Test for Metal Materials; the hardness test is carried out in accordance with "GB / T230.1-2018 Metal Rockwell Hardness Test"; the impact toughness is carried out with reference to "GB / T 229-2007 Charpy Pendulum Impact Test Method for Metal Materials", and the specimen is a "V"-notched specimen; the measurement of martensite and retained austenite in steel is carried out with reference to "YB / T 5338-2019 X-ray Diffractometer Method for Quantitative Determination of Austenite in Steel" and scanning electron microscope backscattered electron diffraction technology.
[0056] Table 1 Performance test results
[0057]
[0058] As can be seen from Table 1, the comprehensive mechanical properties of Examples 1 to 3 are significantly better than those of the comparative examples. Comparative examples 1 and 3 have low impact absorption energy and are prone to cracking, resulting in failure of the wear-resistant parts. The high content of bainite in comparative example 2 causes a decrease in material hardness.
[0059] The above descriptions are merely embodiments of the present invention. It should be pointed out that, for those skilled in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the technical principles of the present invention. These changes, modifications, substitutions and variations should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength low-alloy wear-resistant steel, characterized in that: The chemical composition is as follows by mass percentage: C: 0.28-0.38%, Mn: 1.2-1.5%, Si: 1.6-2.2%, Cr+Mo<1%, V: 0.005-0.015%, rare earth RE: 0.002-0.01%, S≤0.03%, P≤0.03%, and the balance is iron and unavoidable impurities; The final structure of the high-strength low-alloy wear-resistant steel consists of martensite, residual austenite and a small amount of carbide particles, the martensite is lath martensite, and the volume fraction of martensite is ≥92%; The high-strength low-alloy wear-resistant steel has a hardness of ≥52 HRC, an impact absorption energy of ≥16 J at room temperature, and a tensile strength of ≥1800 MPa; The method for preparing the high-strength low-alloy wear-resistant steel comprises the following steps: (1) Mixing scrap steel, ferrosilicon, electrolytic manganese, ferrochrome, ferromolybdenum and ferrovanadium in proportion to the chemical composition of high-strength low-alloy wear-resistant steel, smelting in a medium-frequency induction furnace, deoxidizing and deslagging to obtain qualified molten steel, and raising the temperature of the molten steel to 1620-1650°C; (2) drying and preheating the granular lanthanum-cerium alloy at 200° C., and then evenly spreading it on the bottom of the ladle, and then pouring the molten steel obtained in step (1) into the ladle, and allowing it to stand for a long time for modification; (3) pouring the molten steel modified in step (2) into a casting at a temperature of 1540-1580° C., and after the casting is cooled to below 200° C., heat treatment is performed in sequence to obtain high-strength low-alloy wear-resistant steel; The specific steps of heat treatment in step (3) are as follows: 1) Homogenization annealing treatment: heating the low alloy wear-resistant steel to 950-1000°C at a rate of ≤80°C / h, and then cooling to room temperature in the furnace; 2) Quenching treatment: the annealed steel is heated to 900-950°C at a rate of 80-100°C / h and then water-cooled to room temperature; 3) Tempering treatment: The steel parts after the above quenching treatment are heated to 100-300℃ at a rate of ≤80℃ / h and then taken out of the furnace and air-cooled to room temperature.
2. The high-strength low-alloy wear-resistant steel according to claim 1, characterized in that: In step 2) of the method for preparing high-strength low-alloy wear-resistant steel, when the water is cooled to room temperature, the water pool needs to be fully stirred, and the water temperature does not exceed 60° C. during the quenching process.
3. The high-strength low-alloy wear-resistant steel according to claim 1, characterized in that: The heat treatment holding time is calculated according to the thickness of the casting, and the calculation method is (1+(thickness / 20mm)*1) hours. During heat treatment, the distance between the stacked steel parts is ≥2*thickness.
Citation Information
Patent Citations
High-strength and high-tenacity excavator bucket tooth and production method thereof
CN105568141A
High-abrasion-resistance and high-strength-toughness steel bar of steel for excavator bucket teeth and preparation method thereof
CN112195417A
A heat treatment method for wear-resistant bucket teeth for super-large excavators
CN116377189B
High-strength steel sheet and method for producing same
CN102884218A
Wear-resistant alloy cast steel as well as preparation method and application thereof
CN115976413A